Evaluation of some physical-chemical properties of wheat, cassava, maize and cowpea flours for bread making (2010)
"Both the physical and chemical characteristics of flours affect their quality and the subsequent products from them. The comparative evaluation of particle size, moisture content, bulk density, color, water absorption capacity, pasting viscosity, fat and protein contents of wheat, cassava, maize and cowpea flours were determined using standard methods. Composite breads were produced from 50:30:20, 60:20:20, 70:20:10; 80:10:10, 85:10:5 and 90:5:5 ratio of wheat-cassava/maize -cowpea flours; respectively. Breads produced were subjected to sensory and proximate analyses. The particle size, moisture content, bulk density, water absorption capacity, fat and protein contents of wheat, cassava, maize and cowpea flours are as follows: 154-343 µm, 13.3-14.9% db, 327.4-497.5 kg/m3, 31.9-221.8 g/g, 1.01-2.3% and 2.6-19.39%. Wheat flour had the lowest pasting temperature of 56.1C. Significance differences at P < 0.05 were recorded between most of the properties of the flours. Composite bread of 85% wheat, 10% cassava, 5% cowpea; 90% wheat, 5% cassava, 5% cowpea; and 90% wheat, 5% maize, 5% cowpea were accepted by a sensory evaluation panelist. Substitution with cowpea fruit improved the protein content of the bread."